Impact of colistin-initiation delay on mortality of ventilator-associated pneumonia caused by A. baumannii - Shaher Samrah; Yazan Bashtawi; Wail Hayajneh; Basima Almomani; Suleiman Momany; Yousef Khader (Journal of Infection in Developing Countries)
Introduction: There has been increased incidence and high mortality in cases with ventilator-associated pneumonia (VAP) caused by colistin-only-susceptible Acinetobacter baumannii (COS-AB). Colistin has emerged as a therapeutic option for VAP caused by multidrug-resistant Gram-negative organisms including COS-AB. A retrospective study was conducted to examine the impact of early versus late initiation of colistin on 30-day mortality of critically ill patients with VAP caused by COS-AB. Methodology: Critically ill patients with VAP caused by COS-AB who received colistin were enrolled. The receiver operating characteristic (ROC) curve was used to identify the temporal breakpoint that maximized the difference in 30-day mortality. Results: A total of 56 patients (34 men and 22 women) were included in the study. About 86% of all cases were late-onset VAP. The 30-day mortality was 46.4%. The rate was higher among patients with admission Acute Physiology and Chronic Health Evaluation II (APACHE II) score > 18 and patients with a delay of more than four days in initiating colistin treatment. The mortality rate was 26.9% among patients with treatment delay of four or fewer days and 63.3% for patients with a treatment delay of more than four days. Conclusions: A delay of four days or more in initiating colistin in patients with VAP caused by COS-AB significantly increases mortality. Colistin should be considered in the empirical protocols in late-onset VAP cases when COS-AB is highly suspected.